Genomic fingerprints of uropathogenic Escherichia coli isolated from patients in Babylon province - Bareq Al-lateef; Zainab Al Zibaidy; Zainab Nabat (Journal of Health and Biology, 2026)
The 95 isolates obtained from patient were confirmed as E. coli by 16S rRNA gene the REP-PCR was used to examine (22) E. coli strains that were obtained from patients yielded genomic profiles with five to sixteen bands and many DNA fragments with sizes ranging from 150 bp to 10,000 bp, as appeared, the genetic profiles in respect to the reference strain E. coli the phylogenetic tree that was produced shows the relationships between the various strains under study, the vertical straight line at 88% on the dendrogram indicates the strains' family tie is positively correlated. The phylogenetic tree analysis reveals that the strains under study are diverse. Twenty-two groupings were therefore produced. The genetic profiles with respect to the reference strain E. coli; the phylogenetic tree that was produced shows the relationships between the various strains under study. The vertical straight line at 88% on the dendrogram indicates that the strains' family tie is positively correlated.